Motivation and Reward Analysis of Muay Thai Athletes from the DKI Jakarta Regional Training Center Who Won Medals at the 21st PON Aceh – North Sumatra 2024 - Dia Putri Ananda Lubay; Setyo Riyanto (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the dynamics of motivation and rewards for Jakarta Regional Training (Pelatda) Muay Thai athletes who won medals at PON XXI Aceh-North Sumatra 2024. Athletic performance depends not only on physical and technical abilities but is also influenced by psychological factors including motivation and reward systems. The research employed a qualitative approach with case study design, involving four informants representing all medal-winning athletes (1 silver, 2 bronze) through total sampling technique. Findings reveal the dominance of intrinsic motivation (77%) over extrinsic motivation (23%), with consistency and motivation maintenance strategies as the most critical aspects. Results validate Self-Determination Theory in the Indonesian athlete context and support Achievement Goal Theory with task orientation dominance complemented by ego orientation in national competitions. Jakarta’s reward system successfully creates a supporting environment that fulfills athletes’ autonomy, competence, and relatedness needs. Recommendations include optimizing intrinsic rewards through self-development programs, enhancing more competitive extrinsic reward systems, strengthening performance supporting factors, and developing sustainable reward policies focused on long-term development processes. Further research is recommended using longitudinal and mixed-method approaches with sample expansion to other martial arts sports.